PENTINGNYA PEMAHAMAN LOCA (LETTER OF COORDINATION AGREEMENT) DAN STD 08 PADA SUMBER DATA TERHADAP PENGAJUAN NOTAM DI PIA WILAYAH SURABAYA - Helmalia Rahmasari; Elfi Amir; Endang Sugih Arti; Dini Wagini; Rini Sadiatmi; Togi Adnan Maruli Sinaga; Novita Ayu Permatasari; Mochamad Faisal Muzaki; Andika Eric Firmansyah (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
There is a case of NOTAM submission regarding changes to airport operating hours that occurred in the PIA Surabaya Region. Where there is a discrepancy in the raw data between item D) sent by UPBU Tunggul Wulung which submitted a NOTAM for changes to ATS Hours for VFR Night Flight activities with Standard 08. So the AIS duty on duty coordinated with the NOTAM Office and in the end decided to NOTAM requests are made per day or per activity. Based on these problems, it is hoped that the data source will read and understand the procedures in Standard 08 to make them clearer. It is recommended that item D) not be included if there is a request for NOTAM publication regarding changes to operating hours Keywords: NOTAM, submission, changes